Working culture and continuing education, a coherent binomial for the teachers of Working Education - Díaz Rodríguez, Liudmila; Hernández Nodarse, Tania; Pérez Medina, Maricela (Varela Journal, 2021)
The postgraduate education for the teachers who impart Working Education has not sufficiently pondered the importance of developing a working culture through its contents, or the substantial distinctions within its organizational forms, taking into account both the role of teachers in the Cuban Secondary Education Model and the singularities of the subject. Thus, this paper aims to identify, through a critical analysis, the strengths and weaknesses related to this matter. The study used the dialectical materialist method as a general method of science, where it is possible to achieve an organic integration between the quantitative and the qualitative paradigms. Ten Junior High Schools in the municipality of Santa Clara were chosen as a favourable environment. The groups and individuals were selected by a non-probabilistic sampling. To obtain the data, interviews and a survey (questionnaire as an instrument) were administered to the teachers. The results allowed to approach the aspects achieved in their continuing education and those still susceptible to improvement, as a starting point to transform this reality through a study of greater complexity implying a renewal of this process.